2007
DOI: 10.1016/j.bbabio.2007.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural–functional state of thylakoid membranes of wheat genotypes under water stress

Abstract: Plants were grown in field conditions in the wide area under normal water supply and severe water deficit. Two wheat (Triticum aestivum L.) genotypes contrasting by architectonics and differing in drought-resistance were used: Giymatli-2/17, short stature, with broad and drooping leaves, drought-sensitive, and Azamatli-95, short stature, with vertically oriented small leaves, drought-tolerant). It was found out that Giymatli-2/17 was characterized by relatively low content of Chl a-protein of PS I (CP I) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 37 publications
6
20
0
Order By: Relevance
“…Water stress damages thylakoid membranes, disturbs their function, and ultimately decreases photosynthesis and crop yield (Shah and Paulsen 2003, Huseynova et al 2007, Zhao et al 2007). Stay-green mutants are characterized by increased stability of chloroplast membranes and chlorophyll-protein complexes , Park et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Water stress damages thylakoid membranes, disturbs their function, and ultimately decreases photosynthesis and crop yield (Shah and Paulsen 2003, Huseynova et al 2007, Zhao et al 2007). Stay-green mutants are characterized by increased stability of chloroplast membranes and chlorophyll-protein complexes , Park et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Photochemical activity of chloroplasts isolated from control and drought-stressed plants were followed polarographically as O 2 evolution at 20°C using a water-jacketed Clark-type oxygen electrode chamber under illumination with saturating white actinic light (Huseynova et al 2007). Chloroplast concentrations equivalent to 100 lg Chl were used for all measurements.…”
Section: Assay Of Ps II Activitymentioning
confidence: 99%
“…This causes not only a substantial damage to photosynthetic pigments, but it also leads to deterioration of thylakoid membranes. In the last years, many experimental evidences have suggested that the chloroplast is the main site of ROS production and the primary site of damage of abiotic stresses: various abiotic stresses (cold, light, and drought) with different mechanisms impair the chloroplast function and lead to the production of reactive oxygen species (due to the overexcitation of the photosystem) that may damage chloroplast proteins, membranes, and pigments (Huseynova et al 2007;Huseynova 2012;Anjum et al 2011;Kannan and Kulandaivelu 2011). Oxidative stress can lead to inhibition of the photosynthesis and respiration processes and, thus, plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Stress damages the thylakoid membrane, disturbs its functions, and ultimately decreases photosynthesis and crop yield (Shah and Paulsen 2003, Huseynova et al 2007, Zhao et al 2007. Preservation of the photosynthetic apparatus is an important strategy for enhancing crop yield under stress.…”
Section: Introductionmentioning
confidence: 99%